Komunikasi Getok Tular Pengantar Popularitas Merek - Harjanto, Rudy; Mulyana, Deddy (Mediator, 2008)
Word of mouth (WOM) is a self-spreading chained series of communication in a certain community. The term ‘mouth’ was derived from the fact that the mode of message delivery in WOM is mainly orally, informally, and personally—reflecting the ways we had been talking each other in daily conversation. Technological advance has broadening the scope of WOM. Through the Internet, WOM appears in many digital communication features such as website, online profile pages, personal blog postings, and of course, exchanging mails. WOM, in many ways, has enriched conversation content by exchanging information, knowledge, views, and so on. In a collectivist society like Indonesia, WOM melted—in fact integrated within families (family, clans, working class, etc.). Traditionally, WOM occured when people interested in certain topic. As a form of communication, WOM could be developed as reference channel to popularize a brand (product). This is due because audience believe more to message delivered by somebody they know or respected by them.